Admixture mapping of severe asthma exacerbations in Hispanic/Latino children and youth. Issue 3 (30th September 2022) - Herrera-Luis, Esther; Mak, Angel C Y; Perez-Garcia, Javier; Martin-Gonzalez, Elena; Eng, Celeste; Beckman, Kenneth B; Huntsman, Scott; Hu, Donglei; González-Pérez, Ruperto; Hernández-Pérez, José M; Mederos-Luis, Elena; Sio, Yang Yie; et al.
Abstract : Background: In the USA, genetically admixed populations have the highest asthma prevalence and severe asthma exacerbations rates. This could be explained not only by environmental factors but also by genetic variants that exert ethnic-specific effects. However, no admixture mapping has been performed for severe asthma exacerbations. Objective: We sought to identify genetic variants associated with severe asthma exacerbations in Hispanic/Latino subgroups by means of admixture mapping analyses and fine mapping, and to assess their transferability to other populations and potential functional roles. Methods: We performed an admixture mapping in 1124 Puerto Rican and 625 Mexican American children with asthma. Fine-mapping of the significant peaks was performed via allelic testing of common and rare variants. We performed replication across Hispanic/Latino subgroups, and the transferability to non-Hispanic/Latino populations was assessed in 1001 African Americans, 1250 Singaporeans and 941 Europeans with asthma. The effects of the variants on gene expression and DNA methylation from whole blood were also evaluated in participants with asthma and in silico with data obtained through public databases. Results: Genomewide significant associations of Indigenous American ancestry with severe asthma exacerbations were found at 5q32 in Mexican Americans as well as at 13q13-q13.2 and 3p13 in Puerto Ricans. The single nucleotide polymorphism (SNP) rs1144986 ( C5orf46 ) showed consistent effects for severe asthma exacerbations across Hispanic/Latino subgroups, but it was not validated in non-Hispanics/Latinos. This SNP was associated with DPYSL3 DNA methylation and SCGB3A2 gene expression levels. Conclusions: Admixture mapping study of asthma exacerbations revealed a novel locus that exhibited Hispanic/Latino-specific effects and regulated DPYSL3 and SCGB3A2 .